"The FEMEN body can do everything": Generating the agentic bodies of social movement through internal and external rhetorics. Issue 4 (2nd October 2019) - Chevrette, Roberta; Hess, Aaron
ABSTRACT: Recent theorizing recognizes the body's importance in resistant performances characterizing the streets and screens of contemporary activism. In this essay, we examine how the transnational feminist organization FEMEN constructs embodied agencies through material and mediated means. Rather than focusing only on public appearances, we draw from fieldwork with FEMEN, utilizing participatory critical rhetoric to also examine the internal rhetorics shaping protest activities. Analyzing how FEMEN's training prepares and produces individual, collective, and entangled bodies extends the communicative study of social movements by attending to corporeal molding behind the scenes. FEMEN constructs a gestural routine that enables activists to reexperience their bodies through rhetorics of powerful vulnerability, challenging gendered discourses while increasing rhetorical agency through enacted resistance and embodied solidarities.